Deciphering microbiome and neuroactive immune gene interactions in schizophrenia - Severance, Emily G. (Neurobiol Dis, 2018)
The body’s microbiome represents an actively regulated network of novel mechanisms that potentially underlie the etiology and pathophysiology of a wide range of diseases. For complex brain disorders such as schizophrenia, understanding the cellular and molecular pathways that intersect the bidirectional gut-brain axis is anticipated to lead to new methods of treatment. The means by which the microbiome might differ across neuropsychiatric and neurological disorders are not known. Brain disorders as diverse as schizophrenia, major depression, Parkinson’s disease and multiple sclerosis appear to share a common pathology of an imbalanced community of commensal microbiota, often measured in terms of a leaky gut phenotype accompanied by low level systemic inflammation. While environmental factors associated with these disease states might contribute to intestinal pathologies, products from a perturbed microbiome may also directly promote specific signs, symptoms and etiologies of individual disorders. We hypothesize that in schizophrenia, it is the putatively unique susceptibility related to genes that modulate the immune system and the gut-brain pleiotropy of these genes which leads to a particularly neuropathological response when challenged by a microbiome in dysbiosis. Consequences from exposure to this dysbiosis may occur during pre- or post-natal time periods and thus may interfere with normal neurodevelopment in those who are genetically predisposed. Here, we review the evidence from the literature which supports the idea that the intersection of the microbiome and immune gene susceptibility in schizophrenia is relevant etiologically and for disease progression. Figuring prominently at both ends of the gut-brain axis and at points in between are proteins encoded by genes found in the major histocompatibility complex (MHC), including select MHC as well as non-MHC complement pathway genes.